2019
DOI: 10.1186/s13287-019-1456-x
|View full text |Cite
|
Sign up to set email alerts
|

Human fetal skin-derived stem cell secretome enhances radiation-induced skin injury therapeutic effects by promoting angiogenesis

Abstract: BackgroundRadiation dermatitis is a refractory skin injury caused by radiotherapy. Human fetal skin-derived stem cell (hFSSC) is a preferable source for cell therapy and skin tissue regeneration. In the present study, we investigated the repair effect of using hFSSC secretome on a radiation skin injury model in rats.MethodsWe prepared the hFSSC secretome and studied its effects on the proliferation and tube formation of human umbilical vein endothelial cell (HUVEC) in vitro. Furthermore, we used a Sr-90 radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
2
44
1
Order By: Relevance
“…Moreover, hFSSCs secretome treatment is more effective than of hUCMSCs secretome in resolving brosis, such as some indicators included collagen area, MDA, Hyp, TBIL, and γ-GT. The reasons for the differences in the result between hUCMSCs, and hFSSCs secretome may be due to the difference in the presence more biological activity factors contain in hFSSCs secretome than hUCMSCs secretome [13]. Our studies indicated that hFSSC secretome is an attractive emerging option for therapeutic applications as a therapeutic strategy for liver brosis.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…Moreover, hFSSCs secretome treatment is more effective than of hUCMSCs secretome in resolving brosis, such as some indicators included collagen area, MDA, Hyp, TBIL, and γ-GT. The reasons for the differences in the result between hUCMSCs, and hFSSCs secretome may be due to the difference in the presence more biological activity factors contain in hFSSCs secretome than hUCMSCs secretome [13]. Our studies indicated that hFSSC secretome is an attractive emerging option for therapeutic applications as a therapeutic strategy for liver brosis.…”
Section: Discussionmentioning
confidence: 78%
“…Recently, fetal mesenchymal stem cells functional secretome analysis illustrates that 737±80 protein identi cations were obtained from the amniotic uid-mesenchymal stem cells (AF-MSCs) secretome, interestingly, it reveals that Annexin-A1 as an important paracrine factor in hepatic regeneration [22]. However, the previous study demonstrated that hFSSC presented with the characteristics of both MSC and embryonic stem cell (ESC) [13]. These may be the partial reason that hFSSC secretome can effectively reduce liver brosis, and has better effects than hUCMSC secretome in some indicators levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations